Observation of new resonances decaying to Dπ and D∗π in inclusive e+e− collisions near √s=10.58 GeV - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We present a study of the D+π−, D0π+, and D*+π− systems in inclusive e+e−→c¯c interactions in a search for new excited D meson states. We use a data set, consisting of ∼454 fb−1, collected at center-of-mass energies near 10.58 GeV by the BABAR detector at the SLAC PEP-II asymmetric-energy collider. We observe, for the first time, candidates for the radial excitations of the D0, D*0, and D*+, as well as the L=2 excited states of the D0 and D+, where L is the orbital angular momentum of the quarks.
Im Titel ist [ast] als Tropfensternchen dargestellt und hochgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
BABAR Collaboration: P. del Amo Sanchez, A. Adametz, J. Marks, U. Uwer [und viele weitere]
Im Titel sind da Plus- und das Minuszeichen hochgestellt
Gesehen am 23.08.2023